Customer Satisfaction in Local Coffee Shops: The Integrated Effects of Service Quality, Online Customer Reviews, and Store Atmosphere - Ni Kadek Juli Antari Dewi; Anak Agung Putu Agung; Ni Made Satya Utami (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
This study aims to determine the influence of service quality, online customer reviews, and store atmosphere on customer satisfaction. A quantitative research method was used. The population consisted of all customers at the Pandang Kopi coffee shop. A sample of 100 people was used. The data analysis techniques used were validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, the coefficient of determination, the F-test, and the t-test. The results of the study indicate that service quality has a positive and significant effect on customer satisfaction, online customer reviews have a positive and significant effect on customer satisfaction, and store atmosphere has a positive and significant effect on customer satisfaction. The researcher’s recommendations include: Pandang Kopi Coffee Shop should continue to supervise its employees in providing service, ensure timely service, ensure customer satisfaction, and encourage more positive reviews. They should also reorganize the store layout if it is not yet neat and attractive, and ensure that the products provided to consumers meet established standards.